2020
DOI: 10.1016/j.jsxm.2020.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of RestoreX Penile Traction Therapy in Men with Peyronie’s Disease: Results from Open Label and Follow-Up Phases

Abstract: Background: A randomized, controlled clinical trial evaluating the efficacy of RestoreX traction therapy in men with Peyronie's disease (PD) has been completed, with the 3-month results previously reported. The present study presents outcomes from the open-label and follow-up phases of the original trial. Aim: To report 6-month (open-label phase) and 9-month (follow-up phase) outcomes from a randomized, controlled trial (NCT03389854). Methods: A randomized controlled trial was performed from 2017 to 2019 in 11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 18 publications
1
16
1
Order By: Relevance
“…Improvements in erectile function were also observed in a RCT evaluating the efficacy PTT in men with PD. 12,14 As with the current study, improvements achieved the minimally clinically significant threshold and provide further supporting evidence for an impact of therapy on erectile function. Although the exact mechanism for these improvements is unknown, potential explanations could include tensile-force mediated release of nitric oxide and upregulation of nitric oxide synthase, as demonstrated in animal models and human vascular studies, or diminished fibrosis (ie preserved penile length) leading to lower rates of venous leak.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Improvements in erectile function were also observed in a RCT evaluating the efficacy PTT in men with PD. 12,14 As with the current study, improvements achieved the minimally clinically significant threshold and provide further supporting evidence for an impact of therapy on erectile function. Although the exact mechanism for these improvements is unknown, potential explanations could include tensile-force mediated release of nitric oxide and upregulation of nitric oxide synthase, as demonstrated in animal models and human vascular studies, or diminished fibrosis (ie preserved penile length) leading to lower rates of venous leak.…”
Section: Discussionsupporting
confidence: 76%
“…Results are consistent with other RestoreX PTT studies which have shown improvements ranging from 1.3–2.3 cm in other cohorts. 12,14,18 This contrasts with the previously cited VED RCT, where no statistically significant increase in length was noted in the VED arm compared to baseline. 10 Interestingly, in the current study, control men were found to have no changes in objective penile length (+0.3 cm) after 6 months, despite 59% reporting subjective losses, consistent with other reports.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…No significant change in the mean curvature was observed in the control group (n = 39). 86 Joseph et al 87 performed a RCT comparing PTT with no intervention (3:1) on 110 patients. The PTT resulted in approximately 18−21% mean curve reduction, significantly improved compared with the control group, and 61% of the patients in the PTT group reported a reduction in penile curvature at 6 months.…”
Section: Penile Traction Therapymentioning
confidence: 99%
“…Andropenis [Andromedical, Madrid, Spain], PeniMaster [MSP Concept GmbH & Co. KG, Berlin, Germany], X4 Labs [X4 Labs Canada Inc., Vaudreuil‐dorion, Quebec, Canada], Phallosan Forte [Orbisan Ltd, San Gwann, Malta]), Restorex PTT (RxPTT) introduced several characteristics which allowed greater application of traction forces, including a modified penile clamping mechanism (which displaces force more broadly to the head of the penis), counterbending (not applicable in the current study), stronger mechanical springs, wider displacement base (to better displace the greater forces), and dynamic adjustment of traction during use. Due to these changes, initial clinical trials of RxPTT in men with Peyronie's disease demonstrated consistent improvements in length and curve with 30 min of daily use, compared to variably effective outcomes with 2–9 h of daily use required for first‐generation devices [9–14]. Unexpectedly, the data also demonstrated improvements in erectile function, which was of unclear significance initially.…”
Section: Introductionmentioning
confidence: 99%